BASIC SOCIOCULTURAL AND EDUCATIONAL CONCEPTS OF THE CONCEPT OF LABOR (Scientific journal of the Fergana State University, 2026)
The article explores the sociocultural and educational concepts of diligence as one of the key categories of moral education and spiritual development of the individual. Based on the analysis of philosophical, sociological, and pedagogical literature, the multidimensional nature of diligence is revealed - as a moral value, a cultural phenomenon, and a pedagogical goal. It is argued that diligence serves as an integrative characteristic of the individual, reflecting the level of civic maturity, moral responsibility, and social engagement. Special attention is given to the cultural and historical preconditions of labor perception in different civilizations - from traditional work ethics to modern concepts of professional self-development. In the context of globalization and digital transformation, the problem of fostering diligence acquires new relevance, since labor becomes a field of creativity and self-realization rather than merely physical activity. The article examines pedagogical approaches to cultivating diligence in education: fostering discipline, initiative, respect for labor results, and social responsibility. The author emphasizes the necessity of systemic cooperation between family, school, and society in forming a culture of labor as both a sociocultural and educational value. As a result, diligence is defined not only as a personal trait but also as a fundamental prerequisite for sustainable social development, embodying the harmony between moral, spiritual, and economic dimensions of human activity.